Electrospun antimicrobial hybrid mats: Innovative packaging material for meat and meat-products - Amna, Touseef (J Food Sci Technol, 2014)
To prevent the development and spread of spoilage/pathogenic microorganisms via meat foodstuffs, antimicrobial nanocomposite packaging can serve as a potential alternative. The objective of this study was to develop a new class of antimicrobial hybrid packaging mat composed of biodegradable polyurethane supplemented with virgin olive oil and zinc oxide via electrospinning. Instead of mixing antimicrobial compounds directly with food, incorporation in packaging materials allows the functional effect at food surfaces where microbial activity is localized. The nanofibers were characterized by SEM, EDX, XRD and TEM. The antibacterial activity was tested against two common foodborne pathogens viz., Staphylococcus aureus and Salmonella typhimurium. The present results indicated that incorporation of olive oil in the polymer affected morphology of PU nanofibers and nanocomposite packaging were able to inhibit growth of pathogens. Thus; as-spun mat can be used as prospective antimicrobial packaging, which potentially reduces contamination of meat/meat-products. Moreover, introduced biodegradable packaging for meat products could serve to replace PVC films and simultaneously help to protect natural environment.